2019
DOI: 10.1016/j.bbmt.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Doses of Antithymocyte Globulin in Reduced-Intensity Conditioning Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: The appropriate dose of antithymocyte globulin (ATG) to be used in reduced-intensity conditioning (RIC) allogeneic hematopoietic stem cell transplantation (allo-HSCT) is yet to be determined. We retrospectively analyzed the outcomes of patients who underwent unrelated or mismatch related RIC allo-HSCT for hematologic malignancies and received r-ATG (4.5 mg/kg, 141 patients) versus R-ATG (6 mg/kg, 216 patients). There was a higher incidence of cytomegalovirus (P < .001) and Epstein-Barr virus viremia (P =.03) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Whereas there was not any dose-dependent effect of GRA reported in the literature, several studies have reported that increased dose of THY is correlated with more frequent infections (29,30) and less effective T-cell recovery (6). In our study, platelet counts did not depend on the dose of THY.…”
Section: Discussioncontrasting
confidence: 80%
“…Whereas there was not any dose-dependent effect of GRA reported in the literature, several studies have reported that increased dose of THY is correlated with more frequent infections (29,30) and less effective T-cell recovery (6). In our study, platelet counts did not depend on the dose of THY.…”
Section: Discussioncontrasting
confidence: 80%
“…The method used to diagnose PTLD was not detailed in one study. The length of follow-up was an important source of variation between studies; in some cases the follow-up period was not reported [31,32,34,40,46,48,52,55,59,61,63,73,81,83,86,90,94,98,100].…”
Section: Resultsmentioning
confidence: 99%
“…To compare our results with those reported by Efebera et al [1], we performed a retrospective subanalysis of 121 consecutive patients who underwent 10/10 matched unrelated donor allo-HSCT under the described protocol. The median patient age was 59 years (range, 18 to 74 years).…”
Section: To the Editormentioning
confidence: 88%
“…We read with interest the recent article by Efebera et al [1]. The curative effect of reduced-intensity conditioning (RIC) allogeneic hematopoietic stem cell transplantation (allo-HSCT) relies mainly on a graft-versus-leukemia effect, and the safety of in vivo T cell depletion in this setting is not well established [2,3].…”
Section: To the Editormentioning
confidence: 99%